Effectiveness Of Dates Extract And Oxytocin Massage On Increasing Breast Milk Production For Breastfeeding Mothers - Aprilina Aprilina; Dian Lestari (Poltekkes Kemenkes Surakarta, 2022)
Backgrounds: The problem of insufficient breast milk production causes stress for mothers and hinders exclusive breastfeeding programs. This study aims to see how breastfeeding mothers can produce breast milk when they consume date extract and are given oxytocin massage. Methods: This study used an experimental research design (posttest with control group design), with a purposive sampling technique, inclusion and exclusion criteria, and the inclusion criteria were drawn for grouping. The control group was breastfeeding mothers given oxytocin massage only, while the treatment group was breastfeeding mothers given oxytocin massage and date palm extract simultaneously. Each group consisted of 20 samples. The measurement of breast milk volume was conducted on day 7th and day 14th of postpartum. Results: The results showed that there was no significant difference on the 7th day of measurement in all groups, while on the 14th day of measurement there was a significant difference in breast milk production in the group of mothers who were given date palm extract and oxytocin massage simultaneously, with a p-value of 0.000. Conclusion: Date palm extract and oxytocin massage were very effective when given simultaneously to breastfeeding mothers in increasing milk production, so it was a good solution for breastfeeding mothers.